Bank Liability in Trustee Agreement in Insolvency Status - Franciska Mifanyira; Indah Dwi M. J.; Mega Dwi A (Kanun Jurnal Ilmu Hukum, 2019)
A trust agreement is a special agreement in banking gives the bank the right and authority to manage the customer's assets as stated to the agreement The assets of trust assets are the property of the customer, the management of the assets must be separately carried out to implement the Prudential Principle and Pacta Sunt Servanda in banking contract. This Legal Research use normative positivist with the using of Statute and Conseptual Approach along with three research sources. This Legal Research focus on the Legal Consequences in the Trustee Agreement and Liability of Bank in the case of Bank include the Settlor’s asset as the Insolvency Asset. The Research result are Bank only as a manager of Asset so every legal conduct must have approval of Settlor so If the asset is included the Insolvency Asset is a contract and law violation so it should be fixed by the contractual dispute settlement. Tanggung Jawab Bank dalam Trustee Agreement pada Keadaan Kepailitan Perjanjian kepercayaan adalah perjanjian khusus dibidang perbankan yang memberi-kan hak dan wewenang kepada bank untuk mengelola aset pelanggan sebagaimana dinyatakan dalam perjanjian. Aset kepercayaan adalah milik pelanggan, pengelolaan aset harus dilakukan secara terpisah untuk menerapkan Prinsip Kehati-hatian dan Pacta Sunt Servanda dalam kontrak perbankan. Penelitian Hukum ini menggunakan metode positivis normatif dengan menggunakan undang-undang dan pendekatan konseptual bersama dengan tiga sumber penelitian. Penelitian Hukum ini fokus pada konsekuensi hukum dalam perjanjian perwaliamanatan dan Pertang-gungjawaban Bank dalam kasus Bank termasuk aset Settlor sebagai Aset Kepailitan. Hasil Penelitian adalah bank hanya sebagai manajer Aset sehingga setiap tindakan hukum harus memiliki persetujuan Settlor sehingga jika aset dimasukkan Aset Aset Kepailitan adalah kontrak dan pelanggaran hukum sehingga harus diperbaiki dengan penyelesaian sengketa kontrak.